Evaluating the novel Cinta Hari-Hari Rusuhan by Faisal Tehrani through the lens of Genuine literature - Abu Bakar, Nur Fatiha Fadila (Human Resources Management Academic Research Society (HRMARS), 2024)
This paper is based on a critical reception of Faisal Tehrani's novel titled Cinta Hari-Hari Rusuhan. Most reader considers Cinta Hari-Hari Rusuhan as a serious literature novel that explores themes of the marginal society’s struggle. However, some scholars and literary critics deny the assertion that Cinta Hari-Hari Rusuhan is a serious novel. Significantly, the opposition to this claim is accompanied by the argument that Cinta Hari-Hari Rusuhan is a pulp novel. The clash between these two contrasting perspectives on the status of Cinta Hari- Hari Rusuhan as a literary work is problematized in this paper. Therefore, this paper seeks to analyze the novel Cinta Hari-Hari Rusuhan and subsequently articulate its position. To unravel these issues and achieve the goals of this study, it adopts Mohd. Affandi Hassan's Genuine Literature concept as an analytical framework. This choice is deemed appropriate and relevant since Genuine Literature provides the only local literary theory that seriously and consistently discusses questions regarding the status of literary works. Furthermore, Genuine Literature emphasizes taklif philosophy as a core point of discussion, thus opening room for evaluating the position of literature grounded in Islamic worldview perspectives. This also considers the strength of Faisal Tehrani's religious educational background, making the selection of Genuine Literature justified. In addition to offering theoretical aspects, Genuine Literature also presents several analytical tools such as narrative axis and narrative space. Based on analysis findings, it can be concluded that Cinta Hari-Hari Rusuhan follows “lust- based love” as its narrative axis. To develop this narrative axis effectively, specific storytelling elements such as characters and characterization techniques are employed along with language manipulation. With such a narrative axis and storytelling techniques employed in Cinta Hari-Hari Rusuhan, it becomes evident that it belongs to the category of pulp novels according to the Genuine Literature framework.